(untitled) (Abuja Journal of Sociological Studies, 2026)
The persistent issue of insecurity in Nigeria has emerged as a recurring challenge that jeopardizes the safety of lives and properties. This situation inevitably endangers sustainable development. It has become a significant concern for us as a nation. Government initiatives aimed at tackling this issue, which include public security awareness campaigns, enhancing the capabilities of security agencies, amnesty programs, and job creation, among others, have not produced the expected outcomes. This may be attributed to a lack of political will among leaders at various levels, inconsistencies in policy, and an obsession with wealth. Security is an essential component for sustainable development in Nigeria. Leadership is crucial in shaping national security strategies, especially within the complex context of 21st-century Nigeria. This abstract examines the intricate connection between effective leadership and the various challenges facing Nigeria’s national security. It posits that a modern approach to leadership, defined by strategic foresight, ethical governance, and inclusive decision-making, is vital for confronting contemporary threats such as terrorism, economic instability, and social fragmentation. The abstract highlights the necessity for leaders who can encourage collaboration across different sectors, advance innovation in security management, and foster a sense of national unity to protect Nigeria’s interests in an increasingly interconnected global landscape.